MEASUREMENT FOR IMPROVEMENT: END OF LIFE CARE IN ACUTE HOSPITALS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Kite, Suzanne; Hayes, Anita; Pring, Andrew; Rees, Elizabeth; Verne, Julia; Shouls, Susanna
Abstract : Background: 'Measurement for improvement (MfI)' is a structured methodology to develop and use metrics to support effective change management. 1 2 It differs from measurement for accountability and approaches used in clinical research 3 for example in its use of statistical process control or run charts. 4 There is a need to be able to measure the quality of end of life care (eolc) in acute hospitals. 5 6 There are a number of existing metrics in eolc. 7 8 9 Selecting the best measures to support transformation is a challenge. The Leeds Teaching Hospitals NHS Trust (LTHT) joined the Transforming End of Life Care in Acute Hospitals Programme launched in September 2011 10 which recommended MfI methodologies. Aims: To develop an effective and appropriate set of measures that meet the interests of different groups (patients, families, providers and commissioners) applying the measurement for improvement methodology (meeting aims; real time measurement and reporting, and combining outcome, process and balancing measures). Results: The application of 'Measurement for improvement' methodology to the eolc initiatives of the LTHT, and other acute hospitals in the Transform Programme as appropriate, will be presented. The benefits and limitations of existing metrics in the acute hospital setting will be analysed. Conclusion: Measurement for improvement methodology is a practical methodology with scientific rigour if applied appropriately. Real time measurement supports change in practice. An approach to metrics in this setting will be recommended, for the evaluation of service improvement programmes and to monitor the quality of clinical care. There are known challenges for measurement of eolc in acute hospitals such as the dynamic nature of the patient population, and the crisis nature of hospital admission.